Contact analysis of a drum brake assembly [compact disc] - 290196 Mohd. Zam Abdul Rashid (Skudai : Universiti Teknologi Malaysia, 2006)
Project Paper (Sarjana Muda Kejuruteraan (Mekanikal - Automotif)) - Universiti Teknologi Malaysia, 2006